High efficiency MAPbI3−xClx perovskite solar cell via interfacial passivation. Issue 40 (4th October 2018) - Yuan, Sijian; Wang, Jiao; Yang, Kunlong; Wang, Pengfei; Zhang, Xin; Zhan, Yiqiang; Zheng, Lirong
Abstract : The trap states at the interface between perovskite and charge-transport layer have a great influence on the performance of perovskite solar cells. Abstract : The trap states at the interface between perovskite and charge-transport layer have a great influence on the performance of perovskite solar cells. Here, a high efficiency MAPbI3− x Cl x perovskite solar cell has been demonstrated, by introducing a thin layer of LiF or PbF2 between the SnO2 /perovskite. Improved charge collection and reduced interfacial charge recombination are realized, leading to remarkable rises of both open-circuit voltage ( V oc ) and short-circuit current ( J sc ). This successful interfacial passivation paved a new way to fabricate high performance perovskite solar cells with large V oc .